Effect of Visual Learning Media and Guidebooks on Fluid Restriction Compliance Among Hemodialysis Patients - Suhaemi, Suryati; Nursanti, Irna; Irawati, Diana (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Hemodialysis is vital for patients with end-stage renal disease, and adherence to fluid restrictions is crucial for preventing complications and improving quality of life. However, many patients struggle with fluid intake control due to limited understanding. Objective: This study aimed to assess the impact of visual learning media and guidebooks on fluid intake control, measured by Interdialytic Weight Gain (IDWG), in hemodialysis patients. Methods: A quasi-experimental design involved 26 participants in the intervention group, who received visual media and guidebooks, and 26 controls. IDWG was used to measure fluid restriction compliance. Data were analyzed using t-tests and multiple linear regression. Results: The intervention group showed a significant reduction in IDWG (p < 0.001), indicating improved compliance. Regression analysis found that education level (R² = 0.353, p = 0.008) was a significant predictor of fluid restriction compliance. Conclusion: Visual learning media and guidebooks significantly improve fluid restriction adherence in hemodialysis patients, leading to a reduction in IDWG. These tools are effective for enhancing patient education and improving clinical outcomes.